Meta-analysis of the relationship between ocular and peripheral serum IL-17A and diabetic retinopathy - Li, Xiaodong; Qin, Wei; Qin, Xuewei; Wu, Dandan; Gao, Chenyuan; Luo, Yinyue; Xu, Mingchao (Frontiers in Endocrinology, 2024)
Purpose:A systematic evaluation and Meta-analysis were performed to determine the relationship between IL-17A levels in ocular aqueous and peripheral venous serum samples and diabetic retinopathy (DR). Methods:PubMed, Embase, Web of Science, and CNKI databases were searched from the time of library construction to 2023-09-20.The results were combined using a random-effects model, sensitivity analyses were performed to determine whether the arithmetic was stable and reliable, and subgroup analyses were used to look for possible sources of heterogeneity. Results:A total of 7 case-control studies were included.The level of IL-17A was higher in the Nonproliferative DR(NPDR) group than in the Non-DR(NDR) group [SMD=2.07,95%CI(0.45,3.68),P=0.01], and the level of IL-17A in the proliferating DR(PDR) group was higher than that of the NDR group [SMD=4.66,95%CI(1.23,8.08),P<0.00001]. IL-17A levels in peripheral serum and atrial fluid were significantly higher in NPDR and PDR patients than in non-DR patients in subgroup analyses, and detection of peripheral serum IL-17A concentrations could help to assess the risk of progression from NPDR to PDR. Sensitivity analyses suggested that the results of the random-effects arithmetic were stable and reliable. Subgroup analyses based on assay method and sample source showed that the choice of these factors would largely influence the relationship between IL-17A levels and DR. Conclusions: Elevated peripheral serum and ocular aqueous humor IL-17A levels in diabetic patients are associated with the risk of DR, IL-17A may serve as a potential predictor or therapeutic target for DR, and IL-17A may be an important predictor of inflammation for the progression of NPDR to PDR.